Le siècle de Kafka. - Borges, Jorge Luis, 1899-1986.; Robert, Marthe; Wiesel, Elie, 1928-2016; Starobinski, Jean (Paris : Centre Georges Pompidou, 1984)
Nemcová ; Avenarius ; Masaryk ; Kubin ; Gordin ; Kafka ; Musil ; Gutfreund ; Brod ; Kubista ; Tucholsky ; Barlach ; Wolff ; Klee ; Döblin ; Lipchitz ; Jesenská ; Brecht ; Hausmann ; Welk ; Benjamin ; Ernst ; Groethysen ; Schulz ; Breton ; Poulet ; Brauner ; Borges ; Starobinski ; Gide ; etc.
Le siècle de Kafka, Centre Georges Pompidou, Paris, 1984
boek
Keywords: Kafka, Franz